Compositional differences in gastrointestinal microbiota in prostate cancer patients treated with androgen axis-targeted therapies. Issue 4 (November 2018) - Sfanos, Karen; Markowski, Mark; Peiffer, Lauren; Ernst, Sarah; White, James; Pienta, Kenneth; Antonarakis, Emmanuel; Ross, Ashley
Abstract Background It is well known that the gastrointestinal (GI) microbiota can influence the metabolism, pharmacokinetics, and toxicity of cancer therapies. Conversely, the effect of cancer treatments on the composition of the GI microbiota is poorly understood. We hypothesized that oral androgen receptor axis-targeted therapies (ATT), including bicalutamide, enzalutamide, and abiraterone acetate, may be associated with compositional differences in the GI microbiota. Methods We profiled the fecal microbiota in a cross-sectional study of 30 patients that included healthy male volunteers and men with different clinical states of prostate cancer (i.e., localized, biochemically recurrent, and metastatic disease) using 16S rDNA amplicon sequencing. Functional inference of identified taxa was performed using PICRUSt. Results We report a significant difference in alpha diversity in GI microbiota among men with versus without a prostate cancer diagnosis. Further analysis identified significant compositional differences in the GI microbiota of men taking ATT, including a greater abundance of species previously linked to response to anti-PD-1 immunotherapy such asAkkermansia muciniphila andRuminococcaceae spp. In functional analyses, we found an enriched representation of bacterial gene pathways involved in steroid biosynthesis and steroid hormone biosynthesis in the fecal microbiota of men taking oral ATT. Conclusions There are measurable differences in the GI microbiota of men receiving oral ATT. We speculate that oral hormonal therapies for prostate cancer may alter the GI microbiota, influence clinical responses to ATT, and/or potentially modulate the antitumor effects of future therapies including immunotherapy. Given our findings, larger, longitudinal studies are warranted.